2022
DOI: 10.1155/2022/8670534
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Hyperspectral Image Analysis of Colon Tissue and Deep Learning for Characterization of Health care

Abstract: Colon cancer is a disease characterized by the unusual and uncontrolled development of cells that are found in the large intestine. If the tumour extends to the lower part of the colon (rectum), the cancer may be colorectal. Medical imaging is the denomination of methods used to create visual representations of the human body for clinical analysis, such as diagnosing, monitoring, and treating medical conditions. In this research, a computational proposal is presented to aid the diagnosis of colon cancer, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Machine learning algorithms, such as deep learning, have been effectively employed for feature extraction and classification recognition of hyperspectral images ( 16 , 80 ). Moreover, the research field has continuously expanded its scope to encompass the classification and recognition of various other subjects including cancer, tumor, and skin ( 64 , 81–83 ), forming a positive development trend that keeps pace with the times.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning algorithms, such as deep learning, have been effectively employed for feature extraction and classification recognition of hyperspectral images ( 16 , 80 ). Moreover, the research field has continuously expanded its scope to encompass the classification and recognition of various other subjects including cancer, tumor, and skin ( 64 , 81–83 ), forming a positive development trend that keeps pace with the times.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, DL via CNN has been proven efficient in extracting further information regarding the cellular characteristics of CRC and spatial features regarding the tumour microenvironment, such as the stroma:tumour ratio and the presence and/or the type of white blood cells infiltrating the peritumoral region, avoiding the inter-observational variability. For this purpose, to avoid artifacts caused by the H&E staining, according to various researchers, infrared microscopy could be a non-inferior alternative; infrared microscopy could enhance details regarding the molecular background of the existing CRC and information concerning the spatial Gastroenterology Review 2023; 18 (3) features of the tumour [41][42][43][44]. For this purpose, both direct infrared microscopic observation of H&E slides or image editing through Fourier transformation have yielded quite promising outcomes, reporting an AUROC up to 0.83 and sensitivity ranging from 69% to 83% depending on the tumour grade [22].…”
Section: And Histopathological Diagnosis Of Crcmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%